2018
DOI: 10.1186/s13098-018-0360-3
|View full text |Cite
|
Sign up to set email alerts
|

Markers of metabolic endotoxemia as related to metabolic syndrome in an elderly male population at high cardiovascular risk: a cross-sectional study

Abstract: BackgroundMetabolic syndrome (MetS) is a cluster of conditions that conjoined represents a 1.5–2.5 fold increased risk of developing cardiovascular disease (CVD). Recent studies have reported that gut dysbiosis and leakage of bacterial components, may contribute to the metabolic disturbances and systemic inflammation observed in subjects with MetS. Chronic exposure to lipopolysaccharide (LPS) has been shown to induce features of MetS in experimental studies. LPS interacts with the innate immune system, facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
30
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 35 publications
6
30
0
1
Order By: Relevance
“…Increased LPS production due to alterations in LPS-related gut bacteria and/or gut barrier function lead to the development of metabolic endotoxemia and associated chronic low-grade inflammation 16,37 . Recent studies have shown associations between markers of metabolic endotoxemia (LBP and sCD14) and systemic inflammation (TNF-α and IL-6) in subjects with obesity and metabolic syndrome 43,44 . Likewise, increasing evidence suggests that the presence of endotoxemia is of substantial clinical relevance to patients with HCC 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Increased LPS production due to alterations in LPS-related gut bacteria and/or gut barrier function lead to the development of metabolic endotoxemia and associated chronic low-grade inflammation 16,37 . Recent studies have shown associations between markers of metabolic endotoxemia (LBP and sCD14) and systemic inflammation (TNF-α and IL-6) in subjects with obesity and metabolic syndrome 43,44 . Likewise, increasing evidence suggests that the presence of endotoxemia is of substantial clinical relevance to patients with HCC 45 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the gut microbiome is a source of lipopolysaccharide (LPS), a major component of the cell wall of Gram-negative bacteria, which is able to trigger inflammation and insulin resistance by binding the TLR4 of immune cells and activating the NF-κB signaling pathway [38]. In patients with the metabolic syndrome, increased blood levels of LPS and of the most important LPS ligand, the LPS binding protein (LBP), have been described and found to be correlated with insulin resistance, further supporting the detrimental role of chronic inflammation in glucose metabolism [39,40,41]. Glucose metabolism is also crucial for established tumors, which are characterized by a pronounced glycolytic signature, the so-called Warburg effect [42].…”
Section: Role Of Inflammation Diabetes and Obesity In Enhancing mentioning
confidence: 99%
“…Clinical symptoms of patients with ARDS therefore in many ways correspond to the pathophysiology seen during severe COVID-19 disease. There is a well-known and established link between high LPS levels in blood and MS (9), and obesity (10).…”
Section: Introductionmentioning
confidence: 99%